Kampanye Online Anti Pornografi: “Pornografi” untuk Kalangan Anak Muda - Darmawan, Andreas James; Putri, Dyah Gayatri (Humaniora, 2014)
Nowadays, the internet technology is getting an opportunity to visit pornographic sites. Thus, more and more people have a dependency with a pornography site that is not easy to be released. Campaign against pornography "porNOgraphy" aims to raise awareness of young people to know the risks as well as providing a solution to escape from addiction to pornography. Both impact and solutions to the campaign message is packaged in audio-visual communication, so it is very persuasive in getting people to stay away from pornography and is expected to be easily understood by the public. Hope on the impact of this campaign is that people are interested in trying the suggestions in order to break away from addiction to pornography and form a strong intention and determination to be able to obtain a successful outcome.